Trends in risk-disclosure practices of South African listed companies - Raemaekers, Kim (My University, 2015)
This research examines trends in risk-disclosures in the annual reports of companies which have a primary listing on the Johannesburg Stock Exchange [JSE]. A risk-disclosure checklist, based on the relevant academic and professional literature, was developed by the researcher and used to quantify changes in the frequency of risk-disclosures from 2010 to 2012. The research also examines the extent to which information is integrated in the annual reports under review, identifying weaknesses for the attention of preparers and users of such reports. Results suggest that there has been an increase in the quantum of risk-disclosure and an increased awareness of the importance of complementing traditional financial reporting with a more comprehensive review of organisations’ key risks and their sustainability in the short-, mediumand long-term. In some cases, however, the added risk-disclosure comes with repetition, the inclusion of generic risk information, and a lack of integration between risk-based disclosures and other key financial and non-financial metrics.
Thesis (M. Com. (Accountancy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2014.